Growth of monolayer graphene on nanoscale copper-nickel alloy thin films. (May 2017) - Cho, Joon Hyong; Gorman, Jason J.; Na, Seung Ryul; Cullinan, Michael
Abstract: Growth of high quality, monolayer graphene on copper thin films on silicon wafers is a promising approach to large-scale, direct graphene device fabrication. However, the presence of potential dewetting issues in the copper film during graphene growth has historically limited this method of device fabrication. This paper shows that the use of a nickel adhesion layer coupled with the copper film helps to mitigate the dewetting problem and produce uniform monolayer graphene growth over 97% coverage on films. The feasibility of monolayer graphene growth on Cu-Ni alloy films as thin as 150 nm in total is demonstrated. During the graphene growth on Cu-Ni films, the nickel adhesion layer uniformly diffuses into the copper thin film resulting in a Cu-Ni alloy, helping to promote graphene nucleation and large area surface coverage. Furthermore, it was found that the use of extremely thin metal catalyst films also constraint the total amount of carbon that can be absorbed into the film during growth, which helps to eliminate adlayer formation and promote monolayer growth regardless of alloying content, thus improving the monolayer fraction of graphene coverage on the thinner films. These results suggest a path forward for the large scale integration of high quality, monolayer graphene into nanoelectronic and nanomechanical devices. Graphical abstract: